The Impact of Covid-19 Pandemic on Customers’ Decision for Using Informal Loan Services: Evidence of Luangprabang Municipality: https://doi.org/10.69692/SUJMRD0901205 - INSOMPHORN, Thanousin; YANGSANXAY, Chahue; PHONPHASITH, bounthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This paper aims to study 1). Study the personal factors of customers who use informal loan services; 2). Factors affecting on the decision to use informal loan services, using 173 questionnaires to collect data from informal borrowers and implied by the ordinary least square regression (OLS). The results of the analysis of personal factors of informal loan services found that the majority of service users are between 31-40 years old, accounting for 69.37%. Females account for 56.65% of all service users and married account for 94.22% with education levels below high school accounting for 34.68%, high school accounting for 34.68% and bachelor's or higher accounting for 30.64%. Also, 75.14% of offline loan service users have irregular or daily incomes, especially workers and retailers. While as the results of the factors affecting on decision to use informal loan services, only the Covid-19 variable and the policy variable have a statistically significant level with a significance level of 0.01 and 0.05, respectively. The results of this research indicated that there is only one variable that has the same results as the studies of previous researchers, especially the policy variable in lending. The income and interest rate variables do not effect on customers’ decision. Therefore, this issue will continue to be studied. In order to make the research more clearly, the next researchers should use the Factor Component Analysis model, to see which factors are the real determinants. Because the model in this paper is based on variables that existing in theories, it cannot test whether this situation occur in Laos or not. Otherwise, Logistics models can be used to find out the probability of each factor. This study, the data used in the analysis are in the form of Likert Scale, so it can specify only whether there is an effect or not.